Late-Onset Metastasis of Renal Cell Carcinoma into a Hot Thyroid Nodule: An Uncommon Finding Not to Be Overlooked. (5th January 2015) - Foppiani, Luca; Massollo, Michela; Del Monte, Patrizia; Bandelloni, Roberto; Arlandini, Anselmo; Piccardo, Arnoldo
Abstract : We report the case of a 74-year-old man with a four-year history of right nephrectomy for clear cell renal carcinoma (CCRC) who was diagnosed with hyperthyroidism. On ultrasound (US), a 5 cm solid isohypoechoic nodule with intranodular vascularization was found in the left thyroid lobe. The nodule was deemed autonomous on T 99 m c thyroid scan. Methimazole was started and serum thyroid hormone levels quickly normalized; euthyroidism was maintained with a very low dosage of antithyroid drug. Over time, compressive symptoms and local pain occurred and US revealed growth of the nodule. Total thyroidectomy was performed and the combined histological and immunohistochemical evaluation deemed the nodule compatible with metastasis of CCRC; on 2-year follow-up, no tumor relapse was ascertained. In patients with a history of cancer, a thyroid nodule, even if hyperfunctioning, must be suspected of being a metastasis and investigated. Hot nodules, which are largely benign, may be vulnerable to metastatic colonization owing to their rich vascularization. In these cases, surgery may be curative.